THE ROLE OF RELIGIOUS VALUES IN FACING DISASTERS (Padang City Flash Flood Case Study 2025) - Pausil; Sepriyanti, Nana; Kustati, Martin (International Journal of Multidisciplinary Reseach, 2025)
The flash floods that hit Padang City at the end of November 2025 not only caused physical damage, but also affected the psychological and social conditions of the community. This study aims to analyze the role of religious values in helping communities face and recover from the disaster. Using a descriptive qualitative approach, data was collected through in-depth interviews, participatory observation, and documentation in areas affected by flash floods. Informants included affected communities, religious leaders, volunteers, and disaster management agencies. Data analysis was conducted using the Miles, Huberman, and Saldaña model, including data condensation, data presentation, and conclusion drawing. The results indicate that religious values played a significant role in three main aspects. First, religious values provide a framework of meaning for society in interpreting disasters as tests, destiny, or means of self-improvement, thereby helping to stabilize psychological conditions. Second, religious values encourage positive religious coping strategies such as prayer, trust in God, and collective worship activities that strengthen calm and hope. Third, religious values strengthen individual and community resilience through social solidarity, mutual cooperation, and spiritual support from religious institutions. These findings indicate that religious values play a strategic role in post-disaster recovery and can form the basis for developing faith-based psychosocial support programs.